An evaluation of the physiological uptake range of 18F-fluoro-2-deoxy-D-glucose in normal ovaries of seven dogs using positron emission tomography/computed tomography - Choi, Jinyoung; Chae, Yeon; Kang, Byeong-Teck; Lee, Sungin (Frontiers in Veterinary Science, 2024)
Introduction This study evaluated the physiological uptake range of 18F-fluoro-2-deoxy-D-glucose (18F-FDG) in the normal ovaries of seven dogs using positron emission tomography/computed tomography (PET/CT). Materials and methods The dogs were subjected to general anesthesia and were positioned in ventral recumbency for PET/CT scans. The dosage of 18F-FDG ranged from 0.14 to 0.17 mCi/kg and was administered intravenously followed by 0.9% NaCl flushing; PET/CT images of each dog were obtained precisely 60 min after the injection of 18F-FDG. The regions of interest were drawn manually, and standardized uptake values (SUV) were calculated to evaluate the 18F-FDG uptake in each ovary. The maximum and mean SUVs (SUV max and SUV mean) for all the ovaries of the dogs were then computed. Results The range of SUV max and SUV mean of the normal ovaries of the dogs were 1.28–1.62 and 1.07–1.31 (mean ± standard deviation), respectively. Conclusion This is the first study to investigate the normal 18F-FDG uptake baseline data of normal canine ovaries using PET/CT scans. These data will help clinicians in identifying malignant tumors before anatomical changes in the ovary through PET/CT scans.